Remapping the potential of Gumbrih Village for sustainable tourism management - Gusti Ngurah Joko Adinegara; I Ketut Sirna; Gilbert Nainggolan (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
Tourist villages are a driving factor in increasing tourist visits, but the COVID-19 pandemic has had an impact on the development of tourist villages. The decline in tourist visits and people's income is one of the pandemic's impacts. This research was to examine the potential of Gumbrih Village as a tourist village destination to support sustainable tourism. This study employs a qualitative descriptive method, using the Ministry of Tourism and Creative Economy's tourist village guidelines, which comprise six criteria, as the basis for measurement. The sources of this study were community groups directly involved in tourism services and the village government. The study showed that Gumbrih Village is still suitable as a tourist destination, but some of its tourism potentials are decreasing in number. This is due to a decline in tourist visits, limited financial support, environmental changes, and a lack of coordination in marketing programs. Cooperation between the government and the private sector is necessary to support the sustainable tourism program of Gumbrih Tourism Village. This includes collaborating with hotels and travel agencies on promotional activities, offering training programs, and providing financial support to the local community.